Design of Child-Friendly SDS (SD) Management Model Development Based on Minangkabau Natural Cultural Values - Irman; Dasman Lanin; Mudjiran; Maria Montessori (Researchparks Publishing, 2022)
This research is based on the background that in general the indicators of child-friendly schools have not been implemented properly. The implementation of Child-Friendly Schools is by the indicators of child-friendly schools in SD in Tanah Datar Sub-district in 2019 obtained 34.38% which can be interpreted that services for the fulfillment of children's rights are not implemented properly. good. This study aims to develop a design of a child-friendly SD management model based on Minangkabau natural cultural values. The research method is development research using the ADDIE model. Data were collected through questionnaires, validation widths, and interviews. Then quantitative data was obtained using descriptive statistics, and qualitative data using data analysis techniques suggested by Miles and Huberman. The results of this study design the development of a Child-Friendly School Management Model Based on Minangkabau Natural Cultural Values named MESRA-SISNIBAM. In the MESRA-SISNIBAM model, management functions are integrated with Minangkabau Natural cultural values to meet children's basic needs (children's interests, non-discrimination, child participation, and protection from violence).